PENGARUH PENGGUNAAN MEDIA AUDIO VISUAL TERHADAP MINAT BELAJAR SISWA KELAS V PADA MATA PELAJARAN IPAS DI SDN 28 SINGKAWANG - Sania Gebril; Slamat Fitriyadi; Zulfahita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the low interest in learning of fifth grade students in the subject of science at SDN 28 Singkawang, so audio visual media is needed to increase interest in learning. The formulation of the problem includes: 1) Does audio visual media affect students’ interest in learning? 2) How big is the influence? 3) How is the interest in learning of students towards audio visual media? The aim is to determine the influence, magnitude of influence, and level of interest in learning of fifth grade students towards the use of audio visual media in science. The study used a posttest only control design with a population of fifth grade students of SDN 28 Singkawang and a saturated sample technique. Data analysis included a descriptive percentage test, a normality test with Excel, and an independent sample t-test at a significance level of 5%. The results of the study showed: 1) Audio visual media has a significant effect on learning interest, as evidenced by the normality test (X2 count: 0.927 control; 0.932 experiment ˃X2 table: 0.920), homogenity test (f count: 4.21), and hypotesis test (t count: -2.494 ˃t table:2.012), so Ha is accepted. 2) The influence is high with an effect size of 0.70. 3) Students’ learning interest increased from the high category (73%) to very high (80%) after using audio visual media. In conclusion, audio visual media has a significant and large effect on the learning interest of fifth grade students in science at SDN 28 Singkawang.